4D Printing of Freestanding Liquid Crystal Elastomers via Hybrid Additive Manufacturing. Issue 39 (29th August 2022) - Peng, Xirui; Wu, Shuai; Sun, Xiaohao; Yue, Liang; Montgomery, S. Macrae; Demoly, Frédéric; Zhou, Kun; Zhao, Ruike Renee; Qi, H. Jerry
Abstract: Liquid crystal elastomers (LCE) are appealing candidates among active materials for 4D printing, due to their reversible, programmable and rapid actuation capabilities. Recent progress has been made on direct ink writing (DIW) or Digital Light Processing (DLP) to print LCEs with certain actuation. However, it remains a challenge to achieve complicated structures, such as spatial lattices with large actuation, due to the limitation of printing LCEs on the build platform or the previous layer. Herein, a novel method to 4D print freestanding LCEs on‐the‐fly by using laser‐assisted DIW with an actuation strain up to −40% is proposed. This process is further hybridized with the DLP method for optional structural or removable supports to create active 3D architectures in a one‐step additive process. Various objects, including hybrid active lattices, active tensegrity, an actuator with tunable stability, and 3D spatial LCE lattices, can be additively fabricated. The combination of DIW‐printed functionally freestanding LCEs with the DLP‐printed supporting structures thus provides new design freedom and fabrication capability for applications including soft robotics, smart structures, active metamaterials, and smart wearable devices. Abstract : A novel hybrid 4D printing method, which integrates laser‐assisted direct ink writing and Digital Light Processing, is developed to fabricate freestanding liquid crystal elastomers (LCEs) "on‐the‐fly" with optional structural or removable materials. Various architectures, including hybrid active lattices, active tensegrities, loading‐bearing actuators, and spatial LCE lattices, can be successfully fabricated.